FILE EXTRACTION TOOL USING WEB ADD-INS CASE STUDY: UTP OBE ACHIEVEMENT RECORD - Md Rais, Nurul Syahira (IRC, 2019)
The application of some forms of data analytics on organization’s stored data has increasingly becoming a norm in most organizations. However, in order to generate valid and meaningful results, huge amount of data is needed. Even though there are many DBMS available for organizations to store their data, many still use Excel spreadsheet to do the same. This leads to data being redundant and dispersed. Hence, this project intends to extract related records from different Excel files into single spreadsheet. With this tool, taking UTP as an example, detail scores for student which are captured for multiple courses can be combined to generate integrated scores to measure OBE achievement. The result from implementing this application, it will lead to increase efficiency of the task. Automation can be used to standardize and enforce processes so that all the staff do the job in a same way without any error or redundant data. Thus, this project is well implemented as planned and the processes not only be identical, but much faster too.